Effects of maternal anemia on low-birth-weight in Sub-Sahara African countries: Systematic review and meta-analysis - Nigus Kabtu Belete; Abebe Gedefaw Belete; Darik Temesgen Assefa; Muluken Bekele Sorrie; Manaye Yihune Teshale (PLoS ONE, 2025)
Introduction Maternal anemia is a major public health concern that affects women globally, with a particularly high prevalence in developing countries, notably in sub-Saharan Africa. This condition is linked to negative birth outcomes, with low birth weight being a common consequence of maternal anemia during pregnancy. Therefore, this study aims to evaluate the effect of maternal anemia on low birth weight in the context of sub-Saharan African countries. Methods This study involved searching electronic databases, including PubMed, Embase, Scopus, Cochrane, and Web of Science, as well as reference lists and citation tracking for additional studies. It included cohort, case control, and cross-sectional studies published in English between January 2015 and June 2024. Data were extracted using Covidence and transferred to Microsoft Excel, then to Stata™ Version 17.0 for analysis. Heterogeneity was assessed with forest plots and the Inverse variance (I2) test. Subgroup analysis, sensitivity analysis, and meta-regression were performed to explore sources of heterogeneity, while funnel plot symmetry was evaluated for publication bias. The meta-analytic effect was summarized using pooled odds ratios, 95% confidence intervals, and I2 tests for heterogeneity. This was registered on the PROSPERO under the identification number CRD42024561098. Result A total of 1213 articles were identified, 71 of which were screened for full-text review, and 21 involving women from sub-Saharan African countries met the inclusion criteria, and were included in this meta-analysis. Women with anemia during pregnancy are at higher risk of giving birth to babies with low birth weight compared to women without anemia (AOR = 3.37; 95% CI: 2.66–4.27; I2: 96.71%). Conclusion Maternal anemia during pregnancy was identified as a significant risk factor for low birth weight. Such that the incidence of low birth weight could possibly be reduced with early identification and proper care of anemia during pregnancy.